The rise of the right English nationalism and the transformation of working-class politics - Winlow, Simon 1972-; Hall, Steve 1955-; Treadwell, James (Policy Press, 2023)
One of the biggest political stories of the past few decades in the United Kingdom and elsewhere has been the growing divide between the working class and the mainstream liberal left, which historically has spoken for them. This book offers a close analysis of that phenomenon by showing how the political scene looks to underemployed white men who have seen their standards of living fall in recent years even as their communities have fractured around them. Rather than cast aspersions or mount arguments about the larger success of society as a whole, 'The Rise of the Right' takes these men and their concerns seriously, showing where their opinions are factually wrong but arguing powerfully that liberal politics must find a way of acknowledging and addressing their legitimate fears and frustrations
Previously issued in print: 2016. - Includes bibliographical references and index
Keywords: English Defence League; Geschichte 2009-2016; Right and left (Political science) / Great Britain / History / 20th century; Right and left (Political science) / Great Britain / History / 21st century; Working class / Great Britain / Attitudes / History / 20th century; Working class / Great Britain / Attitudes / History / 21st century; Gesinnung; Neue Rechte; Arbeiter; Großbritannien